Development of Accounting Learning E-Modules with a Guided Inquiry Approach to Increase Student Learning Motivation in Accounting Computer Subjects - Subari, Adrianus Junaidi; Siswanto, Siswanto (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2024)
The application of the guided inquiry model is an alternative to increase student involvement during the learning process. This research aims to produce a learning E-module. The implication is that the guided inquiry-based accounting E-Module effectively boosts student motivation, makes learning more interactive and practical, and assists teachers in managing the classroom more efficiently. The implications of research on e-module development show great potential in enhancing the quality of learning by leveraging technology. E-modules can expand the accessibility of learning materials, enable more flexible and interactive learning, and support the diversity of learners' learning styles. This type of research is research and development. The results showed that the E-Module developed was feasible to use based on the assessment of material experts, media experts and learning practitioners as well as teacher and student responses. Based on the results of the gain test of 0.49, the learning E-Module was declared effective to increase students' learning motivation. The average value of the practicality test is 47.8 in the interval 42.25≤PR<52, meaning that the developed learning E-Module is very practical. While the results of the paired samples T-test (Sig 0.000 <0.05) concluded that there were differences in learning motivation before using the learning E-Module and after using the E-Module.